Determination of spermatological characteristics of Carrier pigeons (Columba livia domestica) raised by local breeders - Acisu, Tutku Can; Yildirim, Emine; Altundal, Burak; Akarsu, Serkan Ali; Cihangiroglu, Aslihan Cakir; Badilli, Nida; Gur, Seyfettin (Univ Tripoli, Fac Vet Med, 2025)
Background: Pigeons are among the earliest domesticated bird species and are classified into groups based on breeding purposes, such as tumblers, rollers, and Carrier pigeons. Historically used for communication, they are now primarily used in various countries for hobbies, sports, and meat production. The public commonly raises Carrier pigeons (Columba livia domestica), valued for their speed and endurance. Understanding their reproductive traits is crucial for sustainable breeding and local genetic resource preservation. Aim: This study aimed to collect semen from male Carrier pigeons raised by local breeders, assess their spermatological characteristics, and examine the correlations among these traits. To our knowledge, this represents one of the first studies to report detailed semen parameters in Carrier pigeons under controlled conditions. Methods: In the research, six male Carrier pigeons brought to the animal hospital between May and October 2024 were used. Semen was obtained by abdominal massage once per month. Samples were visually inspected for contaminants such as blood, feces, or uric acid, and only clean ejaculates were included. Ejaculates were evaluated individually. Semen volume and concentration were determined. Motility was subjectively evaluated. Morphological evaluations and assessments of sperm membrane integrity were also conducted. Ringer's solution was used as the semen extender. All analyses were conducted immediately after semen collection for evaluation purposes. Results: The average semen volume collected from Carrier pigeons was 9.58 f 1.62 mu l, the average total motility value was 69.67% f 1.89%, and the average semen concentration was 3630.25 f 388.26 x 106 sperm ml-1. The average membrane integrity ratio was 73.58% f 5.61%. Head and tail abnormalities were evaluated separately, with the average head abnormality was 6.74% f 1.00%, the average tail abnormality was 8.72% f 1.34%, respectively. The average abnormal sperm rate was determined to be 15.47% f 1.19%. Conclusion: This study determined the spermatological parameters in Carrier pigeons raised by local breeders, providing baseline semen data, insights into relationships among spermatological parameters, and seasonal effects. Limitations include a small sample size and a limited semen collection period due to the number of pigeons brought to the animal
Keywords: Carrier pigeons; pigeon breeding; sperm; spermatological parameters